The Figurative Language found in Taylor Swift’s Song in the Folklore Album - Eonike Esther Wulandari; Lailatul Musyarofah; Yudy Prasetyo (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the use of figurative expressions in selected songs from Taylor Swift’s Folklore album. It focuses on identifying and interpreting the various literary devices found in six songs: Cardigan, The 1, Mirrorball, My Tears Ricochet, The Last Great American Dynasty, and Invisible String. This research employed a descriptive qualitative approach, using the song lyrics as the primary data source. Data were collected through documentation from official lyric sources and analyzed by identifying, classifying, and interpreting the rhetorical devices based on relevant literary and linguistic theories. The findings reveal the presence of several types of figurative expression, including metaphor, hyperbole, personification, symbolism, simile, and irony. Among these, metaphor is the most dominant, reflecting emotions, memories, relationships, and life experiences through symbolic imagery. Hyperbole and personification are also frequently employed to intensify emotional expression and create vivid mental images, while symbolism, simile, and irony enrich the depth of meaning and narrative complexity of the lyrics. Overall, these literary devices play a significant role in enhancing the album’s aesthetic quality, emotional resonance, and storytelling. The findings demonstrate that contemporary song lyrics can be examined as literary texts and provide valuable insights into the creative use of language in modern music.